2020
DOI: 10.1111/jsr.13242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bright light and an afternoon nap on task performance depend on the cognitive domain

Abstract: Previous research revealed inconsistent effects of bright light or a short nap at noon on alertness and performance across different tasks. The current study aimed to explore whether the effects of bright light and a short nap at noon on task performance depended on the cognitive domain. Bright light (1,200 lx, 4,000 K at eye level), nap (near darkness) and control (200 lx, 4,000 K at eye level) conditions were performed from 1:00 to 1:40 PM on three non‐consecutive days with a counterbalanced order across par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…Regarding the task performance, the previous studies had revealed no consistent pattern of a post-lunch nap on task performance varied in different cognitive domains (5,9,10,23,59). The current findings even revealed an indicator and type of task-dependent impairment of nap deprivation on cognitive performance.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Regarding the task performance, the previous studies had revealed no consistent pattern of a post-lunch nap on task performance varied in different cognitive domains (5,9,10,23,59). The current findings even revealed an indicator and type of task-dependent impairment of nap deprivation on cognitive performance.…”
Section: Discussioncontrasting
confidence: 83%
“…Effects of a nap deprivation on mood were scarcely investigated in previous studies, except one earlier study by Caldwell and Caldwell ( 58 ) suggesting beneficial effects of a post-lunch nap on mood. One recent study by Qian et al ( 59 ) reported that participants who took a short midday nap felt happier than those who stayed awake during post-lunch dip period. Similar to the case of subjective sleepiness, the current study revealed exposure to bright blue-enriched white light in the early afternoon would relieve habitual nappers' negative mood stimulated by nap deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are more in agreement with Latshang et al (2013) who also failed to evoke changes. Additionally, although it has been shown that after naps there is an enhancement of mental activity ( Milner and Cote, 2009 ; Qian et al, 2020 ), our results only showed a slight improvement in cognitive performance. It is possible that, as has been proposed ( McMorris et al, 2017 ), changes become apparent only when arterial oxygen delivery is below a certain threshold.…”
Section: Discussioncontrasting
confidence: 95%
“…Previous studies have also shown that individuals with high self-control ability were inclined to act in a more other-interested manner than those with low self-control ability [ 37 , 38 ], and this pattern was reversed when faced with crisis situations [ 39 ]. The effects of ambient light on state self-control were occasionally reported in previous studies [ 29 , 35 , 40 , 41 , 42 ]. For example, exposure to bright versus dim illuminance (1500 lx vs. 150 lx) could increase participants’ public self-awareness and lead to controlled self-regulation [ 35 ].…”
Section: Introductionmentioning
confidence: 58%